Defeat in Interstate War and the Probability of Political Liberalization. Issue 4 (November 2018) - Goldman, Shlomo O.; Heimann, Gadi
The study examines whether defeat in war increases the probability that states will be involved in an international crisis (as a diversionary policy), enter a process of political liberalization, or alternatively, curtail political rights. More generally, it examines the impact of the leaders' weakness on their tendency to adopt these different strategies in order to overcome internal unrest. We look at defeat in war as an indicator of the leader's weakness since we can assume a strong correlation exists between the two. The results showed a significant positive connection to political rights liberalization, indicating that defeat in war increases the probability of liberalization in political rights but does not significantly increase the probability of de-liberalization and diversionary policies. Therefore, the study strengthens the claim that a leader's weakness tends to push him or her toward initiating political reforms.